1998
DOI: 10.1111/j.2042-7158.1998.tb06181.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sho-saiko-to on the Pharmacokinetics and Pharmacodynamics of Tolbutamide in Rats

Abstract: Although Sho-saiko-to (Xiao Chai Hu Tang), a major Chinese traditional medicine, is frequently prescribed with other synthetic or biotechnological drugs for the treatment of various chronic diseases, there is a dearth of information about interactions between sho-saiko-to and co-administered drugs. This paper reports the effects of Sho-saiko-to on the pharmacokinetics and glucose responses of a sulphonylurea hypoglycaemic agent, tolbutamide, after their oral administration in rats. After oral administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…For example, Xiao Chai Hu Tang and Sho-saiko-To decreased the plasma AUC of prednisolone in rats (Homma et al, 1995); whereas Saiboku-To increased it and Sairei-Tohad no effect. Xiao Chai Hu Tang also decreased the plasma concentration of tolbutamide in rats (Nishimura et al, 1998). However, Xiao Chai Hu Tang also inhibited the gastric emptying and raised intragastric pH, which may contribute to the pharmacokinetic alteration of tolbutamide observed in rats (Nishimura et al, 1998;.…”
Section: G Herb-steroid Interactionsmentioning
confidence: 93%
“…For example, Xiao Chai Hu Tang and Sho-saiko-To decreased the plasma AUC of prednisolone in rats (Homma et al, 1995); whereas Saiboku-To increased it and Sairei-Tohad no effect. Xiao Chai Hu Tang also decreased the plasma concentration of tolbutamide in rats (Nishimura et al, 1998). However, Xiao Chai Hu Tang also inhibited the gastric emptying and raised intragastric pH, which may contribute to the pharmacokinetic alteration of tolbutamide observed in rats (Nishimura et al, 1998;.…”
Section: G Herb-steroid Interactionsmentioning
confidence: 93%
“…We have reported that Shosaiko-to elevated plasma concentrations of tolbutamide up to 1 h after oral co-administration. 18,28) In the present studies, plasma tolbutamide concentration tended to be decreased by pre-treatment of Shosaiko-to up to 40 min after dosing. Thus, the present results were not consistent with our previousˆndings.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, it was also demonstrated that TJ-9 showed an enhancing effect on the initial absorption rate of tolbutamide after oral administration. 12,18) The results of the present studies indicate that the reason for the accelerated absorption of tolbutamide from the gastrointestinal tract does not lie in the dissolution process of this drug. It might be induced by other factors, such as a change in drug transport through the intestinal membrane.…”
Section: Discussionmentioning
confidence: 66%
“…12) Briefly, filtered dissolution medium (50 ml) was added to 100 ml of the internal standard solution (50 mg/ml of chlorpropamide) and 350 ml of an acetonitrile-water mixture (1 : 1), and then shaken for 1 min. After centrifugation at 10000 rpm for 5 min, 10 ml of the supernatant was injected into the chromatograph.…”
Section: Methodsmentioning
confidence: 99%